Growth and Productivity of Sugarcane on Inceptisol and Vertisol Soils - Lestari, Rina Puji; Alazis, Agus Eka; Kusumawati, Anna (Jurnal Biologi Tropis, 2026)
Sugarcane (Saccharum officinarum L.) productivity is strongly influenced by soil characteristics that affect plant growth and yield. This study aimed to compare the growth and productivity of sugarcane cultivated on Inceptisol and Vertisol soils and to identify growth parameters associated with productivity. The research was conducted from April to September 2019 in commercial sugarcane plantations located in Magelang Regency, Central Java (Inceptisol) and Kulon Progo Regency, Yogyakarta Special Region, Indonesia (Vertisol). A field survey was carried out using 54 sampling units consisting of Bululawang (BL) sugarcane cultivated under a fifth-ratoon production system and harvested at 12 months of age. Growth parameters observed included plant height, stem diameter, fresh stem weight, and productivity, while soil analyses included pH, available nitrogen, and soil moisture content. Data were analyzed using correlation analysis and independent sample t-tests at a 5% significance level after testing for normality (Shapiro–Wilk) and homogeneity of variance (Levene’s test). The results showed no significant differences in growth and productivity between sugarcane grown on Inceptisol and Vertisol soils. Soil pH and moisture content differed significantly between the two soil types, whereas available nitrogen content did not. Fresh stem weight exhibited the strongest association with productivity (r = 0.999), followed by stem diameter (r = 0.410). However, this relationship should be interpreted cautiously because sugarcane productivity is closely related to biomass accumulation and correlation does not imply causation. The findings indicate that fresh stem weight is the growth parameter most closely associated with sugarcane productivity. Improving soil fertility and implementing appropriate soil management practices are recommended to optimize sugarcane production in tropical environments.